Endograft migration after thoracic endovascular aortic repair - Geisbüsch, Philipp; Skrypnik, Denis; Ante, Marius; Trojan, Michael; Bruckner, Thomas; Rengier, Fabian; Böckler, Dittmar (Journal of vascular surgery, 2019)
Objective - The objective of this study was to evaluate the incidence, timing, and potential risk factors of late endograft migration after thoracic endovascular aortic repair (TEVAR). - Methods - A retrospective analysis was conducted of 123 patients receiving TEVAR for thoracic aortic aneurysms (TAAs), dissections, penetrating aortic ulcer, intramural hematoma, or traumatic transection between January 2005 and December 2015 with a minimum imaging-based follow-up of 6 months. Imaging analysis was performed by three independent readers. Migration was defined according to the reporting standards as a stent graft shift of >10 mm relative to a primary anatomic landmark or any displacement that led to symptoms or required therapy. A standardized measurement protocol in accordance with the reporting guidelines was used. Median follow-up was 3 years (range, 0.5-10 years). - Results - Migration occurred in nine (7.3%) patients and took place at the proximal landing zone (n = 1), overlapping zone (n = 4), or distal landing zone (n = 5), resulting in type I or type III endoleaks in 44% (n = 4/9) of the cases. All cases of migration with endoleaks underwent reintervention; 75% (n = 3/4) of the migration associated with endoleaks could have been identified on previous imaging before an endoleak occurred. Freedom from migration was 99.1% after 1 year, 94.0% after 3 years, and 86.1% after 5 years. Aortic elongation and TAA were identified as predisposing factors for migration (P = .003 and P = .01, respectively). No influence of the proximal landing zone (zone 0-4), type of aortic arch (I-III), or type of endograft on the incidence of migration was found. - Conclusions - Graft migration after TEVAR occurs in a relevant proportion of patients, predominantly in patients with TAA and aortic elongation. Follow-up imaging of these patients should be specifically evaluated regarding the occurrence of migration.
Gesehen am 21.05.2019